2023
DOI: 10.1002/jnr.25168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electroencephalography effective connectivity in frontal low‐gamma band correlates of emotional regulation after mindfulness training

Abstract: Practicing mindfulness, focusing attention on the internal and external experiences occurring in the present moment with open and nonjudgement stance, can lead to the development of emotional regulation skills. Yet, the effective connectivity of brain regions during mindfulness has been largely unexplored. Studies have shown that mindfulness practice promotes functional connectivity in practitioners, potentially due to improved emotional regulation abilities and increased connectivity in the lateral prefrontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…Reduced alpha-band functional connectivity has also been shown in Mild Cognitive Impairment (Fodor et al, 2021). Increase in long-range functional interactions in the gamma band, also reported by Laukkonen et al in their subject during the NS state, has been previously reported in subjects during mindfulness meditation (Ng et al, 2023)and loving-kindness meditation (Lutz et al, 2004) Split-brain experiments suggest that dissociating the two hemispheres makes it appear that there are two independent conscious agents occupying the same brain, with each one not completely aware of the other's knowledge and actions (Gazzaniga, 2005).…”
Section: Experimental Neurosciencesupporting
confidence: 75%
See 1 more Smart Citation
“…Reduced alpha-band functional connectivity has also been shown in Mild Cognitive Impairment (Fodor et al, 2021). Increase in long-range functional interactions in the gamma band, also reported by Laukkonen et al in their subject during the NS state, has been previously reported in subjects during mindfulness meditation (Ng et al, 2023)and loving-kindness meditation (Lutz et al, 2004) Split-brain experiments suggest that dissociating the two hemispheres makes it appear that there are two independent conscious agents occupying the same brain, with each one not completely aware of the other's knowledge and actions (Gazzaniga, 2005).…”
Section: Experimental Neurosciencesupporting
confidence: 75%
“…The EEG markers identified by Laukkonen et al (2023) as associated with the NS state, namely, reduced long-range functional neural interactions in the alpha band and increased long-range synchronization in the gamma band, have both also been reported for mental states characterizable as conscious states in their own right rather than cessation events, such as REM sleep (Brayet et al, 2017)and mindfulness meditation (Ng et al, 2023). Meta-analyses of EEG investigations with meditators can supply a basis to assess sensitivity and specificity for candidate markers for particular meditative states such as Nirodha-samāpatti, and in turn reevaluate the scope of application of term like 'cessation of consciousness'.…”
Section: Proposed Research Directionsmentioning
confidence: 92%
“…In contrast, increased gamma activity in the left prefrontal region in rTMS-responsive MDD patients has been linked to clinical improvements (Noda et al 2017). In healthy individuals, enhanced gamma connectivity has been observed following mindfulness training, purported to reflect emotion regulation (Ng et al, 2023). The increased gamma connectivity observed in the active treatment as compared to the sham treatment group could reflect a mechanism of tDCS effects.…”
Section: Discussionmentioning
confidence: 99%
“…The electrophysiological activity of the brain is known to use different frequency bands for different purposes. For instance, recently low-gamma oscillations have been found to be involved in emotional regulation, and high-gamma oscillations seem to be involved in speech temporal information [25,26]. However, the self-regulatory neuromodulation processes of the brain are vastly unknown.…”
Section: Data Preprocessingmentioning
confidence: 99%